Challenges and Opportunities in the New Millenium: the Service Sector Beckons - Majmudar, Ankit (Ushus Journal of Business Management, 2021)
The Article briefly summarises the development and impact of the services sector in the new economy, with specific reference to its scope and future in the Indian context.